2016
DOI: 10.4025/actasciagron.v38i1.26661
|View full text |Cite
|
Sign up to set email alerts
|

<b>Nitrogen and molybdenum fertilization and inoculation of common bean with <i>Rhizobium</i> spp. in two oxisols

Abstract: ABSTRACT. The aim of this study was to evaluate the effects of foliar application of molybdenum and small dose of nitrogen at planting on common bean production when using seed inoculation with rhizobia. Two field experiments were conducted, applying a randomized block design and a factorial arrangement (3x2x2) + 1, with three replicates. Treatments consisted of inoculation with Rhizobium spp. (strain CIAT 899 T , strain UFLA 02-100, and uninoculated), foliar application of molybdenum (0 and 80 g ha applied as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…There was no significant variation in nodulation and shoot dry matter production of the inoculated and non-inoculated treatments, which did not differ from the controls that were fertilized or not fertilized with mineral N (Table 3), which has also been observed in other studies (Fonseca et al 2013;Figueiredo et al 2016;Oliveira et al 2016). Fertilization with 40 kg ha -1 of N-urea at planting did not affect nodulation because the low application rate was insufficient to suppress nodulation, as also indicated by Figueiredo et al (2016).…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…There was no significant variation in nodulation and shoot dry matter production of the inoculated and non-inoculated treatments, which did not differ from the controls that were fertilized or not fertilized with mineral N (Table 3), which has also been observed in other studies (Fonseca et al 2013;Figueiredo et al 2016;Oliveira et al 2016). Fertilization with 40 kg ha -1 of N-urea at planting did not affect nodulation because the low application rate was insufficient to suppress nodulation, as also indicated by Figueiredo et al (2016).…”
Section: Introductionsupporting
confidence: 68%
“…Fertilization with 40 kg ha -1 of N-urea at planting did not affect nodulation because the low application rate was insufficient to suppress nodulation, as also indicated by Figueiredo et al (2016). Another possible explanation for this occurrence is that high rainfall, in the order of 300 mm, leached part of the mineral N and stimulated nodulation of the plant in response to the nutritional deficiency induced (Moreira and Siqueira 2006;Figueiredo et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To meet the presuppositions of ANOVA, the data of number of nodules and nodule dry matter were first transformed in (x + 0.5) 0.5 . According to the official protocol for evaluation of viability and agronomic efficiency of strains, inoculants, and the literature (Fonseca et al, 2013;Figueiredo et al, 2016;Pádua Oliveira et al, 2017). This argument is pertinent, even though there is no dependence of the locations on the effects of the treatments on BSY.…”
Section: Discussionmentioning
confidence: 99%
“…and genotype and to the density and activity of soil microorganisms (Moreira, 2008). Thus, high N concentration in the common bean plant are expected in soils with a high degree of fertility or with abundant populations of native rhizobia with high symbiotic efficiency (Ferreira et al, 2009;Figueiredo et al, 2016), conditions which were certainly not found in Patos de…”
Section: ----------------------------------R$ -----------------------mentioning
confidence: 99%